Samuel Beckett and Television - Berettini, Célia (ABEI Journal, 2006)
This article focuses on the plays and adaptation written for television by Beckett, having already explored radio and even cinema, in addition to his works for theatre and texts in prose. With his stated preference for visual language and his obsession with minimalism, nothing better than television; besides, without words, he was able to give an original treatment to subjects previously covered: unhappy love, time, death and loneliness, often through melancholic recollection. He was thus an inventor of “a totally new genre”: “visual poems or without words”, some with music, as Martin Esslin classified these small masterpieces.